Answer:
x = 6
Explanation:
So the equation looks like this:
3(x - 2) = 12
So the first thing we are going to do in this equation is multiply 3 by x and -2 in order to get rid of the parenthesis:
3(x - 2) = 12
(3 * x) + (3 * (-2)) = 12
3x - 6 = 12
Now we are going to add 6 to -6 and what you to one side of the equation you do to the other:
3x - 6 = 12
+ 6 + 6
3x = 18
Now in order to segregate the variable x from 3 we are going to have to divide 3x by 3 and what you do to one side of the equation you do to the other:
3x/3 = 18/3
x = 6
Now in order to check our work we are going to replace the variable x with six in the equation:
3(x - 2) = 12 = 3((6) - 2) = 12
(3 * 6) + (-2 * 3) = 12
18 - 6 = 12
12 = 12
Tada, hope this helps you!!